Transport Planning Model for India Project Leader : Dr. M. Q. Dalvi Volume 2 - Planning Commission (Planning Commission, 1982)
The purpose of this subroutine is to forecast Inter-regional flows of commodities when total supplies and demands for each region are known for the forecasting year. This is achieved through a two-way pro-rata adjustment method developed by Richard stone and known as RAS Balancing Technique, The base year flow matrix is first revised. Through adjustment of row totals to row control totals.
Transport Planning Model for India
UNDP Transport Policy Planning Project